Dynamical sampling in multiply generated shift-invariant spaces. Issue 5 (4th April 2017) - Zhang, Qingyue; Liu, Bei; Li, Rui
Abstract : In this paper, we study the problem of dynamical sampling in multiply generated shift-invariant spaces. We give a necessary and sufficient condition for stable reconstruction of signals in multiply generated shift-invariant spaces. Moreover, we show the condition which can make the dynamic sampling problem in multiply generated shift-invariant spaces into the dynamic sampling problem in . At last, we give a concrete example to show how to transform the dynamic sampling problem in shift-invariant space into the dynamic sampling problem in Our results generalize similar ones for the principal shift-invariant spaces.